THE ANALYSIS OF SACRED SCIENCE AND SECULARISM CONCEPT ACCORDING TO HOSSEIN NASR - Achmad Reza Hutama (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Many people think that religion is no longer entitled to intervene in the world, in other words, religion is a private matter that cannot be carried out in the public sphere. The ideology of secularism that continues to spread from the West has now spread to almost all corners of the world, including countries which are actually Islamic countries. Not a few think that modern people are people who have left the spiritual element. Nasr was the first Iranian student to study at MIT in America, he criticized modern science, he also argued that science has left its role and its proper application. So that he wanted to return to the Sacred Science found in previous religions. This study uses a type of literature research (library research) with a theoretical approach. This study uses critical analysis methods and research studies. The result of this study is that Nasr proposes Sacred Science as a way out of the secularization of science. According to him, faith is not separate from science and intellect is not separated from faith (credo ut intelligam et intelligo ut credam). The function of science is as the main path to the sacred. He did not claim that science was wrong, but that it was its philosophical grounds that he thought transcended boundaries.